Challenges and the Opportunities of Community-Based Innovation in Indonesia - Putu Franciska Fajarini; Okdinawati, Liane (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research examined the challenges and opportunities of community-based innovation in Indonesia by conducting a case study in the Petani Muda Keren (PMK) Bali Community, a pilot community for innovative farming development in Bali province. In addition, the research also provided a knowledge transfer mechanism in the community to explore how innovation diffusion happens in the community. As a group of people with a common interest and mission, a farmer’s community could be an effective place for innovation diffusion by offering emotional support to handle psychosocial issues. Moreover, it could construct its members’ perceptions of technology through social shaping processes. A qualitative case study was applied in the research to explore community-based innovation in Indonesia’s agriculture that highlighted Petani Muda Keren Bali Community. Through observation and in-depth interviews with the community founder and twenty farmers from five regions in Bali, the current research indicates challenges and opportunities of community-based innovation in Indonesia related to several issues, including innovation rate and farmers’ readiness, the perception gap between young and elderly farmer, the inconsistency of young members, and government support and policies to the community.